Pembelajaran Tari Piring Sumatera Barat Menggunakan Metode Latihan pada Ekstrakurikuler di SMA Negeri 1 Tumijajar - Trinandi Hari Widaqdo; Agung Kurniawan; Hasyimkan Hasyimkan (Jurnal Seni dan Pembelajaran, 2017)
The research question in this research was how the process of teaching Piring dance through excercise method. The aim of this research were to describe the process of teaching piring dance. Constructivistic theory was implemented to encourage and to build students activness and creativness which are able to employ their self confidence. Qualitative-descriptive was carried on toward this research. The instruments used in this research were observations sheet, interviews, and documentations. The population of this research were teacher and also 8 students of Senior High School 1 Tumijajar. The procedures in this research were, the teacher show the movement to the students and they were following after the teacher, the students had time for repeating the practice, preparing for the instruments, a students was chosen to practice the movement in front of their friends, and the last, the teacher along with the students made a conclusion and closing. The result of this research showed that the students give good improvements in Piring dance after being taught by the extracurricular class method.Rumusan masalah bagaimana proses pembelajaran tari piring menggunakan metode latihan. Penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran dan hasil pembelajaran tari piring. Teori pembelajaran Konstruktivistik digunakan karena menekankan pada aktivitas siswa dan kreativitas yang dapat menumbuhkan kepercayaan pada dirinya. Desain yang digunakan adalah deskriptif kualitatif. Teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Sumber data penelitinya guru dan 8 siswa SMA Negeri 1 Tumijajar. Langkah-langkah metode latihan adalah guru memberikan contoh ragam gerak lalu siswa mengikuti, siswa diberi waktu pengulangan latihan, menyiapkan alat dan bahan yang akan digunakan, seorang siswa diminta untuk mempraktikkan kembali ragam gerak yang telah diberikan, guru dan siswa membuat suatu kesimpulan dan penutup. Hasil pembelajaran ini mendapatkan kategori baik.Kata kunci : latihan, pembelajaran, tari piring